NEW SPECIES OF THE GENUS NUCLEOSPIRA HALL (BRACHIOPODA) FROM THE LOWER DEVONIAN OF NORTHEASTERN RUSSIA - Baranov V.V.; Alkhovik T.S. (My University, 2004)
Three new species of the genus Nucleospira-N. sphaerica, N. lata, and N. rotunda-are described from the Lower Devonian of Northeastern Russia.
Keywords: brасhiороds; athyridids; Nucleospira; Lоwеr Devonian; Northeastern Russia; Paleozoic::Devonian; Палеозой::Девонская